The occurrence and foraging behavior of the army ant Eciton vagans dubitatum in the Itirapina area, São Paulo State, Brazil (Hymenoptera, Formicidae) - Zara, Fernando José [UNESP]; Toledo, Carlos E.V. [UNESP]; Marques, Renato Matos [UNESP]; Caetano, Flávio Henrique [UNESP] (My University, 2002)
This paper discusses the occurrence of the army ant Eciton vagans dubitatum in a semi-deciduous forest, Itirapina area, São Paulo State, Brazil. Comparisons of bivouac and raiding pattern are done in relation to other subspecies of Eciton vagans.
Keywords: Army ant; Eciton vagans dubitatum; Ecitoninae; Eciton vagans